Geographical imbalances and divides in the scientific production of climate change knowledge. (November 2015) - Pasgaard, Maya; Dalsgaard, Bo; Maruyama, Pietro K.; Sandel, Brody; Strange, Niels
Highlights: Global imbalances in climate change knowledge production and exchange exist. The production of knowledge is biased towards richer regions with cooler climates. Knowledge is structured into modules of countries by geographic, climatic, political variables. Knowledge exchange between modules of countries with common research interests is weak. The imbalanced production of knowledge affects adaptation and policymaking. Abstract: Studies on scientific production of climate change knowledge show a geographical bias against the developing and more vulnerable regions of the world. If there is limited knowledge exchange between regions, this may deepen global knowledge divides and, thus, potentially hamper adaptive capacities. Consequently, there is a need to further understand this bias, and, particularly, link it with the exchange of knowledge across borders. We use a world-wide geographical distribution of author affiliations in >15, 000 scientific climate change publications to show that (1) research production mainly takes place in richer, institutionally well-developed countries with cooler climates and high climate footprints, and (2) the network of author affiliations is structured into distinct modules of countries with strong common research interests, but with little knowledge exchange between modules. These modules are determined mainly by geographical proximity, common climates, and similar political and economic characteristics. This indicates that political-economic, social and educational-scientific initiatives targeted to enhance local research production and collaborations across geographical-climate module borders may help diminish global knowledge divides. We argue that this could strengthen adaptive capacity in the most vulnerable regions of the world.